Settlement of Violations of the Professional Code of Conduct of the West Java Regional Police in Connection With Regulations of The Head of The State Police of The Republic of Indonesia - Sufmi Dasco Ahmad (Journal of Law Science, 2022)
The purpose of writing this thesis is to find out the resolution of violations of the West Java Regional Police Professional Code of Ethics based on the Regulation of the Chief of the Indonesian National Police Number 14 of 2011 concerning the Code of Ethics. Police Profession, and to find out the application of sanctions for violating the Police Code of Ethics Based on the Regulation of the Chief of the Police of the Republic of Indonesia Number 14 of 2011 concerning the Code of Ethics of the Police Profession. The approach method used in this study is a normative juridical approach, namely legal research carried out by examining library materials or secondary data as the basic material to be studied by conducting a search on regulations and literature related to the problems studied. The results of the study illustrate that the resolution of violations of the Police Professional Code of Ethics is carried out if there are reports or complaints submitted by the public, members of the National Police or other sources that can be accounted for, which are submitted to the Propam function bearers at every level of the Polri organization, then a preliminary examination is carried out, a trial is carried out to examine members of the National Police who are suspected of violating the Police Professional Code of Ethics for a final decision, and if it is proven that there has been a violation of the Police Code of Ethics, sanctions will be imposed. The sanctions for violations of the Police Professional Code of Ethics are regulated in Article 21 of the Regulation of the Head of the State Police of the Republic of Indonesia Number 14 of 2011 concerning the Professional Code of Ethics of the Republic of Indonesia Police, that for Police Members who are found to have violated the Police Professional Code of Ethics will be subject to sanctions in the form of disciplinary action and/or or disciplinary punishment, administrative sanctions or dishonorable discharge (PTDH) as members of the National Police.